Multifunctional CaSc2O4:Yb3+/Er3+ one-dimensional nanofibers: electrospinning synthesis and concentration-modulated upconversion luminescent properties. Issue 16 (7th April 2017) - Liu, Meihong; Gu, Ming; Tian, Yue; Huang, Ping; Wang, Lei; Shi, Qiufeng; Cui, Cai'e
Abstract : In this paper, an electrospinning technique was developed to prepare CaSc2 O4 :Yb 3+ /Er 3+ one dimensional (1D) nanofibers for the first time. Abstract : In this paper, an electrospinning technique was developed to prepare CaSc2 O4 :Yb 3+ /Er 3+ one dimensional (1D) nanofibers for the first time. X-ray diffraction (XRD), scanning electron microscopy, transmission electron microscopy and nitrogen adsorption/desorption were utilized to characterize the structure and morphology of the as-prepared nanofibers, indicating that single phase mesoporous CaSc2 O4 :Yb 3+ /Er 3+ 1D nanofibers with a uniform size and morphology can be prepared via the electrospinning technique. The as-prepared CaSc2 O4 :Yb 3+ /Er 3+ 1D nanofibers exhibit strong UCL under the excitation of 980 nm. The cross-relaxation ( 4 S3/2 + 4 I15/2 → 4 I9/2 + 4 I13/2 ) and energy back transfer ( 4 S3/2 + 4 F7/2 → 4 I13/2 + 4 F5/2 ) processes are found to be responsible for the concentration-dependent UCL properties, confirmed by rate equation modeling. Optical thermometry in the temperature range of 298–623 K was recorded using the FIR technique with two green UC emissions in the as-prepared CaSc2 O4 :Yb 3+ /Er 3+ 1D nanofibers. The dependence of the sensitivity on the doping concentration of the Yb 3+ and Er 3+ ions is found. The above results suggest that the as-prepared CaSc2 O4 :Yb 3+ /Er 3+ 1D nanofibers have great potential for the applications of drug delivery and optical thermometers.